Resilient livestock supply chains in Pakistan: adaptive strategies for climate-smart agriculture and food security - Afshar, Muhammad Zaurez; Hussain Shah, Mutahir (Frontiers in Food Science and Technology, 2025)
The agri-livestock sector in Pakistan is of critical interest to the socioeconomic fabric of rural areas and is currently facing the risk of systemic vulnerabilities being exacerbated by climate change. The study is part of the doctoral thesis for performance evaluation of a public sector entity under environmental factors. In this paper, we will discuss adaptive measures toward climate-smart agriculture (CSA) in resilient livestock supply chains, based on a study of agri-livestock public sector organizations. In the study, we combine institutional records, interviews of key players, and thematic analysis research to extrapolate on the main facilitators and barriers to resilience. In the study, we conclude that structural gaps, such as unstructured logistics, lacking governance, insufficient financial inclusion, and gender discrimination, continue to exist; nevertheless, new innovations, such as silage production, solarized cool chain, and digital tracing systems, are developing. As much as interventions by public sector organizations can have local gains, resilience at the system level is limited by misaligning policies, institutional impediments, and inadequate investments in the climate-resistant infrastructure. In the paper, it is indicated that the adaptive capacity of the livestock sector in Pakistan requires a system-wide, coordinated, equity-based recalibration that needs to incorporate CSA principles in line with market access, public–private partnership (PPP), and inclusive governance. The policy recommendations underline the importance of integrated national policies, flexible investment in infrastructure, gender mainstreaming, and financial de-risking procedures to preserve food security and rural livelihoods when faced with intensifying climate risks.